Efecto del abonamiento foliar orgánico (Silmixorgano Mineral) sobre rendimiento de Pepinillo (Cucumis sativus) Híbrido Torneo 143 F-1 HYB Lamas-San Martín - Freitas Guevara, Diana (2016)
The following research work had as purpose to identify and evaluate dose of the compost component mineral (Silmix) with better effect in the performance of the cultivation of cucumber (Cucumis sativus L.) hybrid Torneo 143 F-1 Hyb in the province of Lamas, likewise determine the economic analysis of the treatments under study. We used the Randomized Complete Block Design (RCBD) with five treatments and three replications; also used the SPSS 22 statistical program for obtaining the information in the field; the evaluated treatments were T1 (1 kg/ha), T2 (2 kg/ha), T3 (3 kg/ha), T4 (4 kg/ha) of SILMIX and T0 (control, without application). The variables evaluated were, plant height (cm), number of flowers per plant, number of fruits harvested per plant, diameter of the fruit (cm), fruit length (cm), fruit weight (g), fruit yield (kg) and economic analysis. The results indicate that the plants treated with doses of 4,0 kg.ha-1 of Sil mix (T4) obtained the best agronomic results of performance with 120 446.0 kg.ha-1, in the fruit weight with 466, 1g, in the fruit length with 39,5cm, fruit diameter with 6,1cm, number of fruit per plant with 15,5 fruits and plant height with 179,4cm. In the same way with that treatment we reached the highest value B/C with 2,07 with net profit of S/. 24 379,30 nuevos soles, followed by treatment T3 (30 t.ha-1) with value B/C of 1,08 with net profit of S/. 12457,02 PEN. Other treatments got negative values B/C